Potencialidades da aplicação do processo Fenton e foto-Fenton homogêneo no tratamento de águas residuárias em diferentes escalas operacionais: Uma revisão bibliográfica - Machado, Felipe (Universidade Federal de São Carlos, 2020)
Pollution of water resources, caused in large part by inadequate effluent disposal, is currently one of the major problems that the global and scientific community has been trying to mitigate. In addition, conventional wastewater treatment processes have low degradation efficiency for a variety of recalcitrant and toxic components that remain present after their treatment, thus increasing the magnitude of the problem. As an alternative to this problem, advanced oxidative processes (AOPs) appear that use species with high oxidation power, such as the hydroxyl radical, to degrade and mineralize a wide variety of organic compounds refractory to biological treatments. Among the main AOPs studied by the scientific community, the Fenton and photo-Fenton processes stand out due to their simplicity. This work aims to evaluate the potential of the Fenton and photo-Fenton process in the treatment of wastewater at different operational scales from academic works, books, files available on the internet and renowned and peer-reviewed scientific articles available in the databases Web of Science, Scopus, Science Direct, Scielo, Google Scholar and Capes Journals. With the selected materials, a brief description was made about wastewater, wastewater treatment, AOPs and the Fenton and photo-Fenton processes, in addition to the relationship between AOPs and wastewater treatment. This review also identifies and analyzes the main chemical and photochemical reactors and the main parameters involved in these processes and, finally, illustrates with some examples the use of these oxidative processes on pilot and real scales. With the present work it was possible to verify that the Fenton process is already a reality in the treatment of effluents in full scale and that the costs with the reagents are the main bottlenecks of the process for scaling up.
Potentialities of homogeneous Fenton and photo-Fenton application for wastewater treatment in different operational scales: A review
Keywords: processos oxidativos avançados. Fenton. foto-Fenton. foto-Fenton solar. tratamento de água residuárias; ENGENHARIAS::ENGENHARIA QUIMICA::OPERACOES INDUSTRIAIS E EQUIPAMENTOS PARA ENGENHARIA QUIMICA